2014
DOI: 10.2136/vzj2014.06.0071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ion and Dissolved Organic Carbon Interference on Soil Solution Nitrate Concentration Measurements Using Ultraviolet Absorption Spectroscopy

Abstract: Nitrate is often present in surface water, soil solution, and groundwater at undesirable or toxic levels. This study follows development of an in situ nitrate monitoring probe and examines its performance in the presence of potentially interfering ionic species and dissolved organic carbon (DOC). Ultraviolet (UV) absorption spectroscopy measurements of aqueous NO3− were obtained under conditions where prevalent ionic species (i.e., Na+, K+, Ca2+, Mg2+, NH4+, Zn2+, Cu2+, Mn2+, Fe2+, Fe3+, Al3+, Cl−, H2PO4−, HPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…LA at PC4 for 20 minutes generated typical three peaks of absorbance spectra in PTIO solution injected to special silicon tube which was placed on PC4 just after acupuncture treatment (Figure ). According to previous findings, the first (235 nm) and second (351 nm) peaks were considered to come from NOx, and the third peak (565 nm) came from sGC . To confirm this speculation, standard molecules were analyzed by the same conditions.…”
Section: Resultsmentioning
confidence: 85%
“…LA at PC4 for 20 minutes generated typical three peaks of absorbance spectra in PTIO solution injected to special silicon tube which was placed on PC4 just after acupuncture treatment (Figure ). According to previous findings, the first (235 nm) and second (351 nm) peaks were considered to come from NOx, and the third peak (565 nm) came from sGC . To confirm this speculation, standard molecules were analyzed by the same conditions.…”
Section: Resultsmentioning
confidence: 85%
“…All water samples were first analyzed for nitrate and DOC concentration by standard laboratory protocols. The porewater samples were then examined for absorption at a few specific wavelengths that have been 185 previously suggested for direct nitrate measurement in untreated soil water: (i) 302 nm (Moo et al, 2016), (ii) 235nm (Shaw et al, 2014;Tuli et al, 2009)), and (iii) where the absorbance used for calibration equals the absorbance at 220 nm after subtraction of twice the absorbance at 275 nm (hereafter 220/275 nm) (Armstrong, 1963). An additional measurement at 220 nm, as suggested by (Michael et al, 2017), was also carried out, but there was no significant difference in absorption characteristics compared to the 220/275 nm method.…”
Section: Uv Absorption Characteristics Of Agricultural Soil Porewatermentioning
confidence: 99%
“…Although UV absorbance spectroscopy for nitrate analysis is very common, it has some limitations when applied to natural water samples, which contain a variable concentration of dissolved organic carbon (DOC). Shaw et al (2014) studied the possible interference in UV absorbance spectroscopy for nitrate analyses by the 80 different ions that are commonly found in water samples originated from natural sources. They showed that the main interference is caused by DOC, with the nitrate absorbance signal being completely quenched above 50 ppm DOC (Shaw et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These rapid changes are dictated by irrigation-precipitation pattern, fertilization and cultivation methods, plant uptake, and natural soil biochemical processes (Oren et al, 2004;Thompson et al, 2007;Vázquez et al, 2006). Šimůnek and Hopmans (2009) suggested a passive nitrate uptake model with threshold root-zone nitrate concentration (C max ), which, E. Yeshno et al: Real-time monitoring of nitrate in soils as a key in combination with the root water uptake, sets the maximum nitrate uptake from the root zone. The model imposed a jump in nitrate deep leaching when concentration exceeded the threshold values (C > C max ).…”
Section: Introductionmentioning
confidence: 99%